Cytopathologic follow-up of women with cervical cancer post-radiotherapy: case series - Ruan Carlos G. Silva; Rachel Di Paola V. Figueirêdo; Amanda Cristina O. Silva; Carlos Eduardo Q. Lima; Sibele R. Oliveira; Adrya Lúcia Peres (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Cytopathology, in addition to its role in cervical cancer screening programs, is also an important tool for controlling the efficacy of treatment in women with cervical cancer by monitoring and early detecting residual, recurrent neoplasms or benign reactive changes. In this study, we report eight cases of cytopathologic follow-up of women with cervical cancer post-radiotherapy, assisted by a Center of Oncology in Pernambuco. The main cytological findings post-treatment were described,as well as the histopathological characteristics at diagnosis and the treatments performed.